The Analisis Kondisi Fisik Dan Keterampilan Teknik Dasar Permainan Bolavoli Club Bola Voli BVN Kota Bekasi - Bekasi BVN, Muhammad Fachry; Bujang (Motion: Journal Research of Physical Education, 2025)
This study aims to determine the level of physical condition and technical skills of bolavoli games and to determine the correlation between physical condition and technical skills of bolavoli games. This study uses descriptive research methods, the population and sample are female athletes of the Bekasi City BVN club totaling 12 people. The results of data analysis show that most of the female bolavoli athletes of the Bekasi City BVN club have good physical condition. While the basic technical skills of the game of volleyball are included in the classification of less. For the level of correlation between physical condition and bolavoli technical skills with an r2 value of 0.496. meaning that the magnitude of the influence between physical condition and basic bolavoli technical skills in female athletes of the Bekasi City BVN club is 49.6%, while 50.4% is influenced by other factors, which are not included in the study.